Dimensionamento de um sistema híbrido de geração de energia renovável para atendimento da empresa de saneamento de Tucuruí - SOUSA, Carlos Eduardo Ferraz Souza de (2022)
Faced with the gradual but constant increase in electricity tariffs in the country, new alternatives for generating own energy, known as distributed generation, are increasingly being sought. Renewable energy sources play a key role in sustainability, especially solar energy. This study aims to evaluate the feasibility of replacing the current energy supply of a water distribution authority in the region of Tucuruí-PA, from the local utility company, for a more profitable alternative through the combination of floating solar generation and pumped energy storage. To this end, a survey was carried out of the current energy consumption and how much it represents in costs for the enterprise. Then, the availability and amount of solar energy that could be generated on site was verified, allowing the design of a floating photovoltaic unit arranged in a lake placed in the region. An energy storage system was designed as well, in the form of pumping water to different reservoirs, in order to store the available hydropower energy. For the storage system, hydraulic pumps were selected that would also be used as turbines and, to calculate its behavior, a method for predicting the behavior of the pump as turbine outside the nominal point was applied. Analyzes of the system operation were carried out, so that the system could operate as efficiently as possible. Periods of solar generation were interspersed with generation by pumped storage, thus supplying the energy demand of the studied company. Finally, the study analyzes the revenues and expenses generated by the application of the project, in addition to highlighting the savings that can be made in a few years of use in the energy cost of the enterprise. In 8 years, the projected system acquires autonomy and, in 20, it is possible to save more than 30 million BRL, allowing an expansion of the activities currently carried out or even the investment in other business areas.